2010
DOI: 10.1186/1477-7827-8-59
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of melatonin in ram seminal plasma are correlated to those of testosterone and antioxidant enzymes

Abstract: Background: Some breeds of sheep are highly seasonal in terms of reproductive capability, and these changes are regulated by photoperiod and melatonin secretion. These changes affect the reproductive performance of rams, impairing semen quality and modifying hormonal profiles. Also, the antioxidant defence systems seem to be modulated by melatonin secretion, and shows seasonal variations. The aim of this study was to investigate the presence of melatonin and testosterone in ram seminal plasma and their variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 52 publications
(70 reference statements)
5
72
1
2
Order By: Relevance
“…The improvement of semen quality due to addition of exogenous melatonin recorded in the present study was previously reported (Casao et al, 2010;Ashrafi et al, 2011;Ashrafi et al, 2013;Perumal et al, 2015). Moreover, the addition of exogenous melatonin was significantly improving the percentages of DNA morphology, sperm viability and intact plasma membrane (swelling tails) especially at the optimum (3 mM) level of melatonin was reported in the previous study Perumal et al, 2015).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 72%
See 2 more Smart Citations
“…The improvement of semen quality due to addition of exogenous melatonin recorded in the present study was previously reported (Casao et al, 2010;Ashrafi et al, 2011;Ashrafi et al, 2013;Perumal et al, 2015). Moreover, the addition of exogenous melatonin was significantly improving the percentages of DNA morphology, sperm viability and intact plasma membrane (swelling tails) especially at the optimum (3 mM) level of melatonin was reported in the previous study Perumal et al, 2015).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 72%
“…Moreover, it reduced the production malondialdehyde and cholesterol efflux as preserved in liquid state Perumal et al, 2015). However, many authors reported that MT has beneficial effects on preservation of mammalian sperm and improves the velocity and mobility parameters of spermatozoa (Ashrafi et al, 2011;Ashrafi et al, 2013) and also on semen quality parameters (Casao et al, 2010;Ashrafi et al, 2011;Ashrafi et al, 2013;Perumal et al, 2015).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although seasonality is less marked in male than in female, changes in testicular volume, hormonal profiles, sexual behaviour and semen quality that affect the reproductive performance of rams have been reported (Casao, et al, 2010a). In this sense, the treatment of rams with slow release implants of melatonin during the non-breeding season accounted for increased scrotal diameter and improved the reproductive performance of ewes inseminated during anoestrus with semen from these melatonin-implanted males.…”
Section: Seasonmentioning
confidence: 95%
“…GSHPx is one the main enzymes that protects sperm (Perry et al, 1992;Dacheux et al, 2005) and it catalyzes the reduction of hydrogen peroxide (Halliwell and Gutteridge, 1990). Increased GSPHx activity in ram semen is linked to antioxidant effects and maintenance of sperm viability (Casao et al, 2010). Another seminal plasma molecule known as acidic seminal fluid protein (aSFP) also has actions on the control of oxidative stress in the bovine reproductive tract (Einspanier et al, 1993;Schöneck et al, 1996).…”
Section: Proteins Involved In Sperm Protectionmentioning
confidence: 99%